2020
DOI: 10.21203/rs.3.rs-34207/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A High-Efficiency Energy Harvesting By Using Hydraulic Electromagnetic Regenerative Shock Absorber

Abstract: This article intends a hybrid energy harvesting shock absorber design which comprehends energy harvesting of automobile suspension vibration dissipation. A mathematical model of the energy harvesting prototype is established, and simulation results show that the dissipation energy can be recovered by varying the feed module, thereby got the damping forces ratio at different compression and extension stroke. The energy conversion from hydraulic energy to mechanical energy mainly then mechanical energy converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Kokjohn et al, (2011) showed that ignition timing and combustion rate can be controlled by varying the proportions of each fuel and was able to achieve an indicated thermal efficiency of 53% with negligible NOx and soot. It was also reported that flame propagation did not play a significant role due to presence of very lean mixtures during the start of combustion and that the combustion rate is controlled through chemical kinetics like in HCCI (Zhao, et al, 2020;Iqbal, et al, 2020;Li, et al, 2022;Wu, et al, 2019;Adzuan, & Yusop, 2022;Rangasamy, et al, 2020). Comparatively, Figure 2 shows the various LRF delivery methods; conventional premixed port injection, dual direct injection, and the proposed port injection at the valve for this research.…”
Section: Figure 1 Schematic Of Rcci Combustion Strategymentioning
confidence: 97%
“…Kokjohn et al, (2011) showed that ignition timing and combustion rate can be controlled by varying the proportions of each fuel and was able to achieve an indicated thermal efficiency of 53% with negligible NOx and soot. It was also reported that flame propagation did not play a significant role due to presence of very lean mixtures during the start of combustion and that the combustion rate is controlled through chemical kinetics like in HCCI (Zhao, et al, 2020;Iqbal, et al, 2020;Li, et al, 2022;Wu, et al, 2019;Adzuan, & Yusop, 2022;Rangasamy, et al, 2020). Comparatively, Figure 2 shows the various LRF delivery methods; conventional premixed port injection, dual direct injection, and the proposed port injection at the valve for this research.…”
Section: Figure 1 Schematic Of Rcci Combustion Strategymentioning
confidence: 97%